Cholinergic Machinery as Relevant Target in Acute Lymphoblastic T Leukemia - Dobrovinskaya, Oxana; Valencia-Cruz, Georgina; Castro-Sánchez, Luis; Bonales-Alatorre, Edgar O.; Liñan-Rico, Liliana; Pottosin, Igor (Frontiers in Pharmacology, 2016)
Various types of non-neuronal cells, including tumors, are able to produce acetylcholine (ACh), which acts as an autocrine/paracrine growth factor. T lymphocytes represent a key component of the non-neuronal cholinergic system. T cells-derived ACh is involved in a stimulation of their activation and proliferation, and acts as a regulator of immune response. The aim of the present work was to summarize the data about components of cholinergic machinery in T lymphocytes, with an emphasis on the comparison of healthy and leukemic T cells. Cell lines derived from acute lymphoblastic leukemias of T lineage (T-ALL) were found to produce a considerably higher amount of ACh than healthy T lumphocytes. Additionally, ACh produced by T-ALL is not efficiently hydrolyzed, because acetylcholinesterase (AChE) activity is drastically decreased in these cells. Up-regulation of muscarinic ACh receptors was also demonstrated at expression and functional level, whereas nicotinic ACh receptors seem to play a less important role and not form functional channels in cells derived from T-ALL. We hypothesized that ACh over-produced in T-ALL may act as an autocrine growth factor and play an important role in leukemic clonal expansion through shaping of intracellular Ca2+ signals. We suggest that cholinergic machinery may be attractive targets for new drugs against T-ALL. Specifically, testing of high affinity antagonists of muscarinic ACh receptors as well as antagomiRs, which interfere with miRNAs involved in the suppression of AChE expression, may be the first choice options.